Application of Number Puzzle Game Media for Increase Fine Motor Skills of Children at Aisyiah 1 Kindergarten, Bima City - Riati; Hendra; Nurul Zuhriyah (Literasi: Jurnal Pendidikan Guru Indonesia, 2025)
The purpose of this scientific journal article is to analyze the application of number puzzle games to improve children's fine motor skills at Aisyiah Kindergarten in Bima City. The background context of the research at the location is based on initial observations through classroom action, which revealed that some children were still unable to arrange letters according to rules and sequences, and then experienced difficulty arranging numbers (for example, 1 to 10) in descending (ascending or ascending) logical order. This often occurs because children do not yet understand the relationship between number symbols and the quantity (number) of objects presented, or have not yet mastered the concept of number sequence. The method in this study uses a qualitative descriptive analytical research method, with a classroom action approach. Classroom action research (CAR) is a practical research that is intended to improve classroom learning. Classroom action research also uses direct observation data on the course of the learning model that will be used to convey the digestive system material in class. The data is analyzed through several stages in a cycle consisting of 4 stages, namely, (1) planning, (2) implementation of actions, (3) observation (observation), and (4) reflection. The spiritual form of action work from the cycle in this study is as follows: CYCLE 1. 1.) Planning, 2.) Implementation of Actions, 3.) Observation (observation). CYCLE II. From the implementation of Cycle II based on the reflection of Cycle I, it is an improvement on the weaknesses or failures of learning in Cycle I, Cycle II is an improvement on the weaknesses or failures of learning in the first cycle. The techniques used in this study were tests, observations, interviews, and documentation. Tests were conducted with researchers to measure initial reading abilities (pre-test), direct observations were conducted when the test was given to students, then structured interviews with teachers and students, and documentation and other supporting data related to the research. In conclusion, based on the results of the research above, the application of number puzzle game media plays an effective and practical role in improving fine motor skills in students, because the number puzzle game media can support cognitive development, recognizing numbers, mathematical logistics, solving problems, and has a positive effect in improving fine motor skills in early childhood. Thus, an educator, teacher, and parent can provide stimulus to early childhood in the form of game media with number puzzles to improve fine motor skills in early childhood, preschool children. In addition, game media with number puzzles can be done routinely and continuously to improve fine motor skills in early childhood until the growth and development of early adulthood.